Quelques grammes d’histoire pour des tonnes de riz : produire plus suffira-t-il à éradiquer la faim dans le monde ? - Ben Wisner; Jean-Christophe Gaillard (Développement Durable et Territoires)
This article questions the conclusions of the recent world food security conference held in Rome in June 2008. It challenges the strategy which aims at increasing investments in the agricultural sector as a response to widespread hunger. The discussion relies on examples from Africa and Asia.